DEAF STUDENTES PROGRAM FOR HIGHER EDUCATION ENTRANCE EXAMINATION - Martins, Sandra Eli Sartoreto de Oliveira; Souza, Marcília Correa de; Sanches, Miriãn Caroline (Faculdade de Filosofia e Ciências, 2019)
Discussing and problematizing the participation of minority groups in university educational spaces will require a commitment to break down barriers that impede social participation and equal access to higher education. Based on this premise, this article describes the results of a college entrance examination orientation program for the entry of deaf students into higher education. Twenty-nine deaf participants who completed high school and / or who are attending the EJA - Youth and Adult Education - that resided in the city of Marília / SP, from 2015-2018, participated in the program. The interventions proposed in the program consisted of offering pedagogical orientation activities on the UNESP entrance exam, as well as the accompaniment of deaf students in the activities of the alternative pre-college course, from UNESP / Marília. The meetings were held on a recurring basis during the two months preceding the registration period for the selection processes in the period mentioned. The program prioritized themes that portrayed aspects of the organized forms of the university entrance exam. It allowed participants to recognize themselves on the condition of disability to appreciate the requirements of differentiated care and to dialogue about the rights of participation of all in the selection process for the entrance to Higher Education.